EFEK TRANSPARANSI TERHADAP AKUNTABILITAS DAN KEPERCAYAAN PENGELOLAAN ZAKAT, INFAQ DAN SEDEKAH (ZIS) - Andi Ruslan (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to analyze the effect of transparency on muzakki trust in zakah, infaq and alms (ZIS) management organizations either directly or indirectly through accountability. This research was conducted on 200 ZIS payers at the Zakah Management Organization (OPZ) in Makassar. The data collected through the survey were analyzed by structural equation modeling using AMOS. The results show that the application of transparency in the form of information disclosure on the management of ZIS funds greatly determines the trust of muzakki, transparency in the management of ZIS funds supports the creation of accountability for the ZIS management organization. Accountability contributes to increase the trust of muzakki in the ZIS management organization and transparency can predict muzakki trust if it is mediated by accountability.